AN ANALYSIS OF STUDENTS’ READING COMPREHENSION BASED ON THEIR LEARNING STYLE AT THE FOURTH SEMESTER OF UNISMA - Risalatul Adawiyah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
AbstractIn fact, Reading comprehension is such a complex skill for several students for some reasons; therefore, every student has their own learning style that will ease them to comperhend a text during reading comprehension process. This fact emerges a matter about students’ learning style during reading comprehension process. This case drove the researcher to do an investigation on students’ learning style during reading comprehension process researcher by selecting high reading achievers of English department of University of Islam Malang as the participants of this research. The researcher did a qualitative research by adapting two likert scale questionnaires of VAK Learning Style By O’Brien (1985). Based on the investigation findings, mostly high reading achievers are visual learners with 55% dominated while the rest of the participants are kinaesthetic learners 35% and auditory learners 10%. This finding implicates that, the high reading achiever gain high score for their reading comprehension since they implement some characteristics of being visual learners such as re-writing notes, focusing on visual objects, staying focused in a quiet place, using flashcards, coding, numbers, and other symbols to recall something.Keywords: Reading Comprehension, and Learning Style.